Correlation between copper particle morphology and number of graphene layers on a palladium substrate. (1st January 2023) - Takahashi, Junro; Nakamura, Kengo; Kioka, Yusei; Kato, Hiroki; Yamamoto, Takahiro; Homma, Yoshikazu
Abstract: Metal–metal interactions through graphene can result in interesting phenomena, although the effective range has not yet been studied in detail. This work investigated these interactions by evaluating the contact angles of Cu particles on graphene grown on a Pd substrate. Thermally-induced variations in the morphology of the particles were assessed using in situ scanning electron microscopy, and such changes were also evaluated by conducting molecular dynamics calculations. The contact angle exhibited a marked decrease in going from graphene multi-layers to a mono-layer. The simulations showed the particles on a graphene mono-layer will interact both with the graphene and the substrate.